Significant improvement in the strength of Mg-Al-Zn-Ca-Mn extruded alloy by tailoring the initial microstructure. (March 2019) - Wang, Fang; Zheng, Ruixiao; Chen, Jing; Lyu, Shaoyuan; Li, Yun; Xiao, Wenlong; Ma, Chaoli
Abstract: Mg-4.8Al-4.9Zn-2.3Ca-0.3Mn alloy was extruded using two different billets with coarse and refined initial microstructures, respectively. The extruded alloy using the coarse billet exhibits a good combination of strength and ductility among the reported Mg-Al-Ca and Mg-Zn-Ca alloys, while that using the refined one yields an increase of 66 MPa in tensile yield strength with little ductility loss. This distinct improvement is mainly attributed to the increased dispersion strengthening by the finer and more evenly distributed second particles. In addition, such particles assist in the formation of both ultrafine dynamically recrystallized grains and intense basal texture un-recrystallized grains which can also contribute to the incremental strength. Highlights: Coarse and refined billets were prepared by gravity and die casting, respectively. Extrusion using the coarse billet showed a good combination of strength and ductility. The improved strength with little ductility loss was obtained when using the refined billet. The finer and more evenly distributed second phases caused the significant strength.